Coronavirus disease 2019: International public health considerations. Issue 2 (27th February 2020) - Greene, Christopher J.; Burleson, Samuel L.; Crosby, James C.; Heimann, Matthew A.; Pigott, David C.
Abstract: On December 31, 2019, the Chinese government announced an outbreak of a novel coronavirus, recently named COVID‐19. During the following weeks the international medical community has witnessed with unprecedented coverage the public health response both domestically by the Chinese government, and on an international scale as cases have spread to dozens of countries. While much regarding the virus and the Chinese public health response is still unknown, national and public health institutions globally are preparing for a pandemic. As cases and spread of the virus grow, emergency and other front‐line providers may become more anxious about the possibility of encountering a potential case. This review describes the tenets of a public health response to an infectious outbreak by using recent historical examples and also by characterizing what is known about the ongoing response to the COVID‐19 outbreak. The intent of the review is to empower the practitioner to monitor and evaluate the local, national and global public health response to an emerging infectious disease.